HEV recharge battery algorithm using a fuzzy controller - Aymen, Flah (2017 International Conference on Green Energy Conversion Systems (GECS), 2017)
This paper presents a power management algorithm for an electric vehicle (EV) basing on a battery charging system. The charging system control schemes with the necessary components as the power systems, controller and motor are described. Obtaining the necessary power in the exactly moment and in a specific conditions presents the goal of the presented algorithm. The autonomy EVs are considered as an asset to the automobile district to optimize effective performance economically and environmentally under various operation conditions. A fuzzy logic bloc is used in this work for helping calculating the necessary power that must be injected in the battery through the installed generator. To evaluate the algorithm performance MATLAB/SIMULINK is used and a simulation results are presented and discussed.